2013
DOI: 10.1002/nau.22349
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamic effects of dutasteride add‐on therapy to alpha‐adrenergic antagonist for patients with benign prostatic enlargement: Prospective pressure‐flow study

Abstract: Dutasteride can improve lower urinary tract symptoms by improving storage bladder function and relieving obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 30 publications
7
21
0
Order By: Relevance
“…Also, in the combination study with propiverine, it is thought that the addition of propiverine shows almost the same reduction effect of storage symptoms as the present study . Reduction of the PV was similar between the groups, and similar to that previously reported with an α 1 ‐blocker in combination with dutasteride …”
Section: Discussionsupporting
confidence: 91%
“…Also, in the combination study with propiverine, it is thought that the addition of propiverine shows almost the same reduction effect of storage symptoms as the present study . Reduction of the PV was similar between the groups, and similar to that previously reported with an α 1 ‐blocker in combination with dutasteride …”
Section: Discussionsupporting
confidence: 91%
“…In accordance with previous reports, the present study confirmed that 24‐week treatment of dutasteride reduced prostate size and improved voiding and storage symptoms including urinary urgency. We previously examined urodynamic effects of dutasteride on BOO and bladder storage function and showed that dutasteride relieved obstruction and improved bladder storage function . The present study confirmed the beneficial effect of dutasteride in relieving obstruction and improving bladder storage function.…”
Section: Discussionsupporting
confidence: 86%
“…Wada et al [32] studied the effect in 52 patients receiving dutasteride, in addition to alpha-adrenergic antagonists, if they were not satisfied with their treatment. The authors concluded that long-term dutasteride administration as the adjunct therapy resulted in moderate improvement of the obstructive symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-three articles of highest reliability (inclusion criteria was maximal level of evidence) were selected, 6 of which were dedicated to the monotherapy with PDE5 inhibitors in patients with BPH-LUTS and concurrent BPH-LUTS and ED [1823]; 4 articles reported monotherapy with alpha-adrenergic antagonists in patients with BPH-LUTS [2427]; 5 were dedicated to monotherapy with 5-alpha reductase inhibitors in men with BPH-LUTS [2832]; 7 reported combined therapy with alpha-adrenergic antagonists and PDE5 inhibitors in patients with BPH-LUTS [3339]; 1 reported combined therapy with alpha-adrenergic antagonists and 5-alpha reductase inhibitors in patients with BPH-LUTS [40]. Thirty-one articles – retrospective works, clinical cases and low reliability publications were excluded from the analysis.…”
Section: Methodsmentioning
confidence: 99%